THE EFFECT OF INTRINSIC MOTIVATION, WORK LIFE BALANCE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT CUT NYAK DHIEN HOSPITAL, LANGSA - Shanty Nurhayati S; Em Yusuf Iis; A. Hadi Arifin; Yusniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of intrinsic motivation, work-life balance, and work environment on the performance of employees at Cut Nyak Dhien Hospital, Langsa. This study uses a quantitative method quantified by data collection techniques through questionnaire distribution. The data used in this study are primary data obtained by distributing questionnaires to 121 hospital employees. The population in this study was 121 employees, while the sample was a saturated sampling technique where the entire population was taken. The analysis method used was multiple linear analysis techniques using SPSS 26. Data analysis used validity and reliability tests, classical assumption tests, coefficient of determination tests, f tests, and t tests. The results of this study indicate that intrinsic motivation and work-life balance have a positive and significant effect on the performance of employees at Cut Nyak Dhien Hospital, Langsa, and the work environment has a negative and insignificant effect on the performance of employees at Cut Nyak Dhien Hospital, Langsa.